Creative entrepreneurship: the guidelines of the fashion design sector in Lisbon from the perspective of creative producers (ModaPalavra e-periódico, 2021)
The study presented aims to raise questions about the perception of creative producers and their ability to participate and adapt to the emerging economy model, based on the development of creativity and authoral processes of product creation. To this end, it took into account the transformations observed over the past decade wich presented Lisbon as a city with potential to become an exponente in innovation and creative entrepreneurship. From documentary surveys of recent economic indexes and identification of initiatives, brands and copyright producers, some of the factors that favored the development of the sector were verified. The data that make up the research were based on interviews with entrepreneurial designers, whose speeches provided material for further analysis. The analysis of the perspective of the professionals participating in the research points to factors responsible for the processes that contributed to the restructuring of the economy.
Keywords: creative economy; Lisbon; Design